2018
DOI: 10.1098/rsos.172182
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of eicosapentaenoic acid-enriched phospholipids and sea cucumber saponin on orotic acid-induced non-alcoholic fatty liver disease in rats

Abstract: Non-alcoholic fatty liver disease (NAFLD) is becoming an increasingly prevalent chronic liver disease all over the world. The present study was undertaken to explore the synergistic effects of sea cucumber saponins (SCS) and eicosapentaenoic acid-enriched phospholipids (EPA-PL) at ratios of 0.5 : 0.5 and 1 : 1 on NAFLD and demonstrate possible protective mechanisms. It was found that the combination of EPA-PL and SCS at half dose exhibited better effects than EPA-PL or SCS alone and the combination of EPA-PL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…In light of the literature data, sea cucumber-derived anti-cancer molecules that exhibit this size fall into the categories of triterpenes, glycosaminoglycans, and peptides [8,50]. At present, we cannot exclude the existence of potential synergic activities, as reported by Guo et al [51].…”
Section: Discussionmentioning
confidence: 73%
“…In light of the literature data, sea cucumber-derived anti-cancer molecules that exhibit this size fall into the categories of triterpenes, glycosaminoglycans, and peptides [8,50]. At present, we cannot exclude the existence of potential synergic activities, as reported by Guo et al [51].…”
Section: Discussionmentioning
confidence: 73%
“…The process of β-oxidation is regulated by various enzymes, including ACSL1, CPT1, and CPT2 (Zhou et al, 2015;Guo et al, 2018). Located in the outer mitochondrial membrane, ACSL1 is the rate-limiting enzyme for fatty acid activation (Bonnefont et al, 2004;Warfel et al, 2017); it catalyzes long-chain fatty acids to long-chain acyl-coA; then, fatty acyl-coA is transported to mitochondria by CPT1 and CPT2 for β-oxidation (Eaton, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Saponins were important secondary metabolites and bioactive substances for sea cucumbers. A large number of studies have confirmed that sea cucumber-derived saponins exhibited antitumor, antidiabetes, anti-obesity, antihyperlipidemia, and other functions, which have been widely used in the pharmaceutical and functional food industries. Holothurin A (HA) and Echinoside A (EA) were two major saponins in sea cucumber Pearsonothuria graeffei . Their chemical structures are shown in Figure A,B, which were similar to cholesterol.…”
Section: Introductionmentioning
confidence: 94%